Pelatihan untuk Mengajar Bahasa dan Matematika Berbasis Metode Montessori di Sekolah Dasar - Andri Anugrahana (Jurnal Pengabdian Pada Masyarakat, 2021)
TRAINING TO TEACH LANGUAGE AND MATHEMATICS BASED ON MONTESSORY METHODS IN ELEMENTARY SCHOOLS. An important aspect that determines learning success is the learning method used by the teacher. Teacher prospective teachers should have broad insights related to learning methods. Prospective teachers and teachers need to vary the learning model. Montessori method is one method that follows the natural tendencies of children and teachers need to prepare learning that follows the stages of child development. Based on these thoughts, community service is carried out to help prospective teachers and teachers' insights about the Montessori method. The sequence of community service activities is the training and mentoring of prospective teachers, the implementation of learning by the Montessori method by prospective teachers, evaluation and reflection on the results of implementation, preparation of training materials for elementary school teachers, and the activity ends with the evaluation and training of Montessori methods for elementary teachers. The result of community service is that prospective teachers are happy to have classroom experience and 100% of students are happy because they are involved in innovative learning activities, the Montessori method. In addition, teachers also get experience training in Montessori methods.